Наблюдения над некоторыми особенностями идиолекта М. Цветаевой (на материале блоковского цикла) - Соблис, М. Ю. (Kalbotyra, 1986)
The article deals with a question of the influence of A. Block on the poetry of M. Tsvetayeva. The author investigates a kind of transformation of some poetical themes – namely, the theme of snow and the theme of Christ – in Tsvetayeva’s cycle “Verse to Block”.